Analisis Dampak User Generated Content (UGC) Media Sosial Terhadap Kunjungan Wisatawan Ke Bali - Maha, I Gede Hikaru; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p22, 2023)
Lately, social media has become one of the alternatives for tourists to seek destination recommendations for their travel purposes. One way to obtain information related to these recommendations is through User Generated Content (UGC). UGC refers to content created by users, such as photos, videos, reviews, and other types of content shared through social media. This research aims to analyze the impact of User Generated Content (UGC) on tourists' visits to Bali. The study was conducted by collecting data through an online survey distributed to tourists who have visited Bali. The collected data includes the frequency of UGC consumption, types of UGC consumed, factors influencing tourists' decisions, and the influence of UGC on tourists' expectations and satisfaction. The research findings indicate that UGC has an impact on tourists' visits to Bali, both in terms of pre-visit expectations and the actual travel experience. The results of this research show that User Generated Content (UGC) has a significant influence on tourist visits to Bali. Through consuming User Generated Content (UGC), tourists get several things such as recommendations, information and new insights, especially in making decisions to choose Bali as a travel destination. Apart from that, tourist expectations tend to be high due to User Generated Content (UGC). The quality of User Generated Content (UGC) plays an important role in shaping tourist expectations and experiences because tourists tend to trust realistic and relevant content based on their preferences. Other factors that influence tourist decision making include price, recommendations, location, availability of information, and availability of facilities. The existence of User Generated Content (UGC) as a source of information influences tourists' perceptions of these factors. Keywords: User Generated Content, Social Media, Impact, Tourism